Tactical performance analysis of Malaysian youth karate exponents - Azmi, A.; Malek, N. F. A.; Low, J. F. L. (European Journal of Molecular & Clinical Medicine, 2020)
The aim of this study was to analyse the tactical performance of youth karate exponents during the Malaysia Games, 2018. A total of 104 kumite matches, consisted of 52 men and 52 women were recorded during the games and analysed the frequency of attacking and defending using Longomatch® software. Non parametric Kruskal Wallis statistical analysis was used to compare the effectiveness of attacking and defensive by gender and performance of successful and unsuccessful athletes. The findings of this study showed that the male athletes were more effective in attacking than females. However, no differences by gender in the effectiveness of defending. This study also found that successful exponents were more effective in attacking for male and defending for both gender compared to unsuccessful athletes.